Langkah Progresif Peningkatan Akreditasi Sekolah: Studi SMP di Kota Padang - Novelia, Ira; Azwar, Azwar; Elfitra, Elfitra (Insititut Agama Islam Negeri (IAIN) Curup, 2019)
Accreditation is the recognition and assessment of the authorities on the quality of education in the educational institution. This recognition or assessment is to provide assurance to the community that the institution is feasible and becomes the main reference for the learning process to occur, so that the output is guaranteed and can be used by the community of graduates of the educational institution. Basically, the school always strives to improve the accreditation of its school with the aim that the school gets an accreditation rating that is better than the accreditation value of the previous five years. Therefore, the school is trying to prepare well all the things needed in school accreditation, starting from the preparation stage to the implementation stage of school accreditation. The purpose of this study was to determine the school's efforts to improve school accreditation. This research uses a double hermeneutic approach which is none other than the qualitative research subtype of Giddens with this type of research being descriptive. This study found that the efforts made by the school accreditation team in both SMP Negeri 9 Padang and SMP Negeri 36 Padang were the same effort. The efforts included: filling the accreditation instrument and the accreditation supporting data and information collection (IPDIP) instrument. prepare all accreditation documents and supporting information (IPDIP) of accreditation, complete school accreditation documents / data, take time before going home or on holidays to prepare school accreditation documents, appoint more professional teachers in PBM to be assessed as accreditation assessors, complete facilities and school infrastructure, decorating the accreditation assessment room as attractive as possible, inviting the school committee on the day of the school accreditation assessment